Comprensión lectora en los estudiantes de 7mo año de educación básica - Maigua Caiza, Jenny Elizabeth (2022)
The purpose of this research report is to strengthen reading comprehension in the Language and Literature area, by identifying its level in seventh-year of basic education students from Alfredo Escudero School, in Machachi, Cantón Mejía, from 2021-2022 scholar year. The deductive method was used in this process, the population was made up of 11 students, the Reading Comprehension Test (ACL) was the instrument used with its ACL-6 variant, which evaluates the reading comprehension with a wide perspective from the different types of texts, focusing on the essential dimensions of reading comprehension , which one allowed to show that there is a trouble in the literal, inferential and critical levels, that make up the students' reading comprehension as a whole. That’s why, after carrying out a theoretical investigation , I notice the need to propose and develop a design that lets us to solve the observed problem , which consists of the implementation of interactive worksheets elaborated in the Liveworksheets web page, these ones allow to develop each one reading comprehension levels , after that we can consider that the investigation is viable , due to the topic is very important for the students’ development and also is an interesting fact for teachers. In addition, the results obtained will show us, that the application of interactive worksheets, allow students to improve their reading comprehension levels, in an innovative, creative and playful way, facilitating the construction of their learning.